NEEDS AND INTERESTS OF THE PERSONALITY EXISTENTIAL PROCESSES IN THE CONDITIONS OF DIGITAL SOCIETY: SOCIAL AND PHILOSOPHICAL ANALYSIS (Scientific journal of the Fergana State University, 2026)
The article is based on the study of the interaction of needs and interests with existential processes in a digital society, the disclosure of the conceptual foundations and socio-philosophical aspects of these concepts, contradictions in ensuring the needs and interests of young people in a digital society, as well as ways to ensure the community of individual needs and interests and existential situations in the context of modernization of society.